Responsibility as a Professionally Significant Trait of an Officer of the Penal Correction System of the Russian Federation - Ezhova, O.N.; Ushkov, F.I. (Psihologiâ i pravo, 2021)
This research work is aimed at studying the personality traits of the personnel of the penal correction system (PCS) using the 70-statement questionnaire Multidimensional-Functional Diagnostics of "Responsibility" by A.P. Pryadeyin. Second and fourth year students of Samara Law Institute of the Federal Penitentiary Service, as well as current staff members of correctional facilities of the penal correction system took part in the research work. The study analyzed the naturally-predetermined (operational) and lifetime-acquired (substantial) responsibility domains. The obtained results suggest that the expression degree of personality traits in the PCS personnel that are necessary for the formation of responsibility, is largely determined by age, work experience in the PCS and by gender differences. The results are of practical importance and can be used for the formation of responsibility of the PCS personnel in performance management both during education period and during professional activities. Работа направлена на изучение качеств личности у сотрудников уголовно-исполнительной системы с помощью методики А.П. Прядеина «Многомерно-функциональная диагностика «ответственности» (ОТВ-70). В исследовании принимали участие курсанты второго и четвертого курсов Самарского юридического института ФСИН России, а также действующие сотрудники исправительных учреждений уголовно-исполнительной системы. В ходе проведенного исследования анализировались природно заданная (операционная) и прижизненно приобретенная (содержательная) сферы ответственности. Полученные результаты дают возможность говорить о том, что степень выраженности качеств личности у сотрудников УИС, необходимых для формирования ответственности, во многом определяется возрастом, опытом работы в уголовно-исполнительной системе и гендерными различиями. Полученные результаты имеют практическое значение и могут быть использованы для формирования ответственности у сотрудников уголовно-исполнительной системы при организации служебной деятельности, как в период обучения, так и во время профессиональной деятельности.